Diabetes mellitus en el anciano: Enfermedad heterogénea, de clasificación dinámica y tratamiento predecible. - SECLEN, Segundo; ALVAREZ, Rosa; CHANTRES, María Teresa; SERRANO, Manuel (Revista Médica Herediana, 2013)
In order to evaluate clinical presentation and to determinate classification criteria of type I diabetes (I-DM) in the elderly, we carried out a study in 258 patients more than 60 years old of which 40% used insulin by failure to oral hipoglycemic agents (OHA). The prevalence of ischemic cardiovascular disease was 36%, peripheral vascular disease 34% and stroke 30%; non-proliferative retinopathy 47%, peripheral neurophaty 37% and nephropathy 16%. Obesity (36%), hypertension (33%) and hypercholesterolemia (12%) were evaluated. The average duration of diabetes was 20 years. Postglucagon C-Peptide, HLA-DR antigens and islet cell antibodies (ICA), were measured in 75 older diabetic patients on treatment of which 24 used insulin, 40 OHA and 11 diet. Older patients on insulin had longer duration of disease, less obesity, low basal level of C-Peptide and a low response post glucagon; C-Peptide (0.94+0.5 pmol/ml) compared with patients on diet (1.8+0.9 pmol/ml) and OHA (1.8+0.8 pmol/ml). Older diabetics on insulin therapy had a greater frequency of HLA-DR3 (42%) and HLA-DR4 (21%). The ICA was negative in most patients. This study shows the high prevalence of macrovascular and microvascular disease in elderly patients with diabetes mellitus and that the most reliable parameter in classifying I-DM is the measurement of basal and postglucagon C-Peptide. HLA-DR specific markers can be used with this parameter because their expression is partly shared. This approach appears useful in the older diabetic patients to help classify diabetes and its management.